Upper Ordovician (Sandbian-Katian) graptolite and conodont zonation in the Yangtze region, China - Xu, Chen; Bergstroem, Stig M.; Zhang Yuandong; Goldman, Dan; Qing, Chen (Earth and Environmental Science Transactions of the Royal Society of Edinburgh, 2010)
The graptolite and conodont biostratigraphy of the latest Darriwilian, Sandbian and early and middle Katian succession on the Yangtze Platform is reassessed based on numerous new fossil collections and previously published data. At least at some localities, the lowermost Miaopo Formation is of pre-Nemagraptus gracilis Zone age (uppermost Pygodus serra and lowermost P. anserinus conodont zones). The rest of this formation (except for the uppermost part, which lacks diagnostic graptolites) has a diverse graptolite fauna of the N. gracilis Zone. The uppermost part of the Miaopo Formation contains few biostratigraphically diagnostic graptolites but the occurrence of conodonts of the Baltoniodus alobatus Subzone of the Amorphognathus tvaerensis Zone suggests equivalence with part of the Climacograptus bicornis graptolite Zone. The conodont succession of the Datianba Formation is virtually identical with that of the Miaopo Formation, confirming that these units are coeval. The lowermost part of the overlying non-graptolitic Pagoda Formation represents the upper A. tvaerensis Zone, and its upper part represents the A. superbus Zone. The occurrence of Dicellograptus elegans in the overlying Chientsaokou Formation (equivalent to the Linhsiang Formation in Yangtze Gorges region) suggests equivalence with the Pleurograptus linearis Zone in Scotland, which is consistent with the relatively non-diagnostic conodont fauna in these Chinese units. The biostratigraphic data are in good agreement with the delta C-13 chemostratigraphy and permit the establishment of precise correlations with the Baltoscandic and North American successions.